The work-family conflict of university foodservice managers: An exploratory study of its antecedents and consequences. (March 2015) - Ryan, Bill; Ma, Emily; Hsiao, Aaron; Ku, Minyen
Abstract: This study investigated the issue of work-family conflict (WFC) among university foodservice managers. Multiple regression results showed that Role Conflict and Role Ambiguity were two significant antecedents of WFC. In addition, working on weekends also led to increased levels of WFC. The main finding of the study is that WFC is a significant antecedent of university foodservice managers' intention to leave, indicating that WFC is an important factor that explains the high turnover rate of hospitality employees.